Innovative industrial Cu(In,Ga)Se2 thin film solar cell with high characterization using nanoparticles structure - Ahmed Thabet; Safaa Abdelhady; Khaled Ebnalwaled; Abdallah Ibrahim (IAES Indonesian Section, 2019)
This paper presents new design of ZnO/CdS/CIGS/Mo nanocomposites thin film solar cell based on individual and multiple nanocomposites absorber layer. A theoretical analysis is presented for enhancing the efficiency and characterization of individual and multiple nanocomposites CdS/Cu (In, Ga) Se2 thin film solar cell. Moreover, this paper is achieving high efficiency with a thinner CIGS layer for reducing the direct materials usage and there by the materials costs by adding various metallic nanoparticles in CIGS absorber layer.